Higher wages in exporting firms: self-selection, export effect, or both? First evidence from linked employer-employee data - Schank, Thorsten; Schnabel, Claus; Wagner, Joachim (Review of World Economics, 2010)
While it is a stylized fact that exporting firms pay higher wages than non-exporting firms, the direction of the link between exporting and wages is less clear. Using a rich set of German linked employer-employee panel data we follow over time plants that start to export. We show that the exporter wage premium does already exist in the years before firms start to export, and that it does not increase in the following years. Higher wages in exporting firms are thus due to self-selection of more productive, better paying firms into export markets; they are not caused by export activitie
WiSo-Import:2015-03-26:463
Keywords: Wages; Transformation; Germany; Forschungsbericht 2010; Exports; Exporter wage premium